A Nickelate Renaissance - Mitchell, J. F. (Frontiers in Physics, 2021)
The 2019 discovery of high temperature superconductivity in layered nickelate films, Nd1-xSrNiO2, has galvanized a community that has been studying nickelates for more than 30 years both as cuprate analogs and in their own right. On the surface, infinite layer nickelates, and their multilayer analogs, should be promising candidates based on our understanding of cuprates: square planar coordination and a parent d9 configuration that places a single hole in a dx2-y2 planar orbital makes nickelates seem poised for superconductivity. But creating crystals and films of sufficient quality of this d9 configuration in Ni1+ has proven to be a synthetic challenge, only recently overcome. These crystalline specimens are opening windows that shed new light on the cuprate-nickelate analogy and revealing nuances that leave the relationship between cuprates and nickelates very much an area open to debate further study. This Perspective gives a qualitative, phenomenological account of these newly discovered superconductors and multilayer members of the infinite layer nickelate family. The focus is on our current understanding of electronic and magnetic properties of these materials as well as some future opportunities, explored from the viewpoint of synthetic challenges and some suggested developments in materials discovery and growth to make further progress in this rejuvenated field.